2011
DOI: 10.1111/j.1574-6968.2011.02320.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the genetic variation of reference microbial cultures used within food and environmental laboratories using fluorescent amplified fragment length polymorphism analysis

Abstract: Fluorescent amplified fragment length polymorphism (FAFLP) analysis was applied to genetically fingerprint 'working culture control strains' used by accredited food microbiology laboratories. A working culture control strain is defined as a subculture from a strain initially obtained from an authenticated source [such as the National Collection of Type Cultures (NCTC)] that is maintained for use with routine testing within the laboratory. Working culture control strains from eight food examination laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
2
0
1
Order By: Relevance
“…This finding differs from that of a recent study 30 in which isolates obtained 4 weeks after an episode of respiratory tract disease had no change in M bovis genotype as determined on the basis of PFGE analysis. This is consistent with reported discrepancies between AFLP analysis and PFGE analysis, 15,32 perhaps because of the number of fragments analyzed (mean of 65 fragments in the present AFLP analysis, compared with 6 to 10 fragments in the PFGE analysis in other studies 15,33 ) or differences in the restriction enzymes used (BglII and MfeI vs KpnI, MluI, and SmaI), although the discrepancy may also reflect differences in the interval between sample collections (44 to 50 days in the present study vs 3 weeks) and differences in the nature of the disease in Canadian beef feedlots and French veal feedlots. We considered the following 3 possible explanations for the reason that different samples from the same calf had differences in M bovis AFLP profiles: recombination of the M bovis genome might change the AFLP profile over time, concurrent infection with multiple strains might artifactually lead to identification of different AFLP profiles at the different times, or a calf might eliminate 1 strain of M bovis but become reinfected with another strain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding differs from that of a recent study 30 in which isolates obtained 4 weeks after an episode of respiratory tract disease had no change in M bovis genotype as determined on the basis of PFGE analysis. This is consistent with reported discrepancies between AFLP analysis and PFGE analysis, 15,32 perhaps because of the number of fragments analyzed (mean of 65 fragments in the present AFLP analysis, compared with 6 to 10 fragments in the PFGE analysis in other studies 15,33 ) or differences in the restriction enzymes used (BglII and MfeI vs KpnI, MluI, and SmaI), although the discrepancy may also reflect differences in the interval between sample collections (44 to 50 days in the present study vs 3 weeks) and differences in the nature of the disease in Canadian beef feedlots and French veal feedlots. We considered the following 3 possible explanations for the reason that different samples from the same calf had differences in M bovis AFLP profiles: recombination of the M bovis genome might change the AFLP profile over time, concurrent infection with multiple strains might artifactually lead to identification of different AFLP profiles at the different times, or a calf might eliminate 1 strain of M bovis but become reinfected with another strain.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we considered the possibility that the AFLP type might change over time in a single clone of M bovis, such as by genomic recombination, although this is not likely to induce the magnitude of genetic change required to substantially alter the AFLP profile. 33 Three isolates of M bovis were passaged in vitro every 2 days for 56 days, which was comparable to the duration of the present study. The pairs of M bovis isolates and subcultures had 93.3% to 99.5% homology in AFLP profiles before and after passage, which indicated that there was no change in the AFLP type.…”
Section: Discussionsupporting
confidence: 54%
“…It has been noted that mutations can occur during transfer of bacterial strains between laboratories, when bacteria are often incubated for several days in rich medium transport stabs [30], and also during long-term preservation of stocks within culture collections [42]. Furthermore, even limited passages the laboratory can result in mutations [26,43], which may cause phenotypic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Although still the same serovar, Gram et al [25] reported that a Danish field isolate of serovar 8 had been mixed up with reference strain 405 during routine lab use, leading to confusion over the reported genotype of omlA for this strain [19]. Furthermore, changes in reference strain genomes due to genetic drift following multiple passages in the lab have also been reported for various bacterial species, sometimes leading to phenotypic differences [26][27][28][29]. Genetic changes can also occur following extended incubation over several days in rich medium, such as when agar stabs are used for shipping bacterial strains between research groups [30].…”
Section: Introductionmentioning
confidence: 99%
“…Існує спільна база даних щодо генетичних профілів ідентифікованих штамів. Подальші модифікування методу, серед яких AFLP (Amplifed Fragment Lenght polymorphism), базуються на ферментативній рестрикції, що широко використовується для молекулярної характеристики патогенних мікроорганізмів при епідеміологічних і таксономічних дослідженнях (Cross et al, 2011;Jadhav et al, 2012).…”
Section: вступunclassified